Protective Labour Legislation in Transition: A Critical Appraisal of the New Codes - Ahlawat, Sonika (Trinity Law Review, 2026)
The consolidation of India’s labour laws into four comprehensive labour codes represents one of the most significant policy shifts in the country’s industrial relations framework since independence. Advocated as a means to simplify compliance, enhance ease of doing business, and expand social security coverage, these codes simultaneously raise questions about their adequacy in safeguarding workers’ rights in an increasingly informalized and precarious labour market. This article critically appraises the new labour codes by examining their implications for worker protection, with particular focus on wages, occupational safety, social security, and industrial relations. Drawing upon legal analysis, comparative perspectives, and empirical insights, the paper highlights the tension between economic flexibility for employers and protective guarantees for workers. While the codes offer potential for greater uniformity and inclusion, concerns remain over diluted safeguards, weakened collective bargaining mechanisms, and limited coverage for vulnerable groups. The study argues that the true test of these reforms lies not merely in their legislative intent but in their implementation, enforcement, and capacity to reconcile growth imperatives with the constitutional mandate of social justice.
Keywords: Industrial relations; labour codes; social security; worker protection